Superficial and electrical characterization of thin films based on Chitosan/polypyrrole/MWCNT. (22nd July 2016) - Olarte-Paredes, A.; Salgado-Delgado, R.; Salgado-Delgado, A. M.; Rubio-Rosas, E.; García-Hernández, E.; Vargas-Galarza, Z.
ABSTRACT: In recent decades conducting polymers have attracted attention due to their promising and versatile applications in different fields. There is a considerable interest in the application of nanotubes multilayer carbon (MWCNT) because of their unique structure, high electrical conductivity, high chemical stability, and high surface-to-volume ratio. These properties make MWCNT extremely attractive for fabricating sensors. Composites based on a matrix of a biopolymer such as the chitosan (CS) with a lot of conductive polymers or (MWCNT), have received increasing attention due to their attractive structural, mechanical and electrical properties that could have applications in different fields such as tissue engineering, biomedicine, and manufacture of sensors and biosensors. Have been reported conducting polymer composites with an extensive range of interesting mechanical and electrical properties, which is reported in this paper to obtain films by ultrasonic bath mixing of Chitosan 3% w/v using polypyrrole (PPy) and multilayer carbon nanotubes. Surface characterization was performed using scanning electron microscopy (SEM). The electrical properties were analyzed using electrochemical impedance spectroscopy (EIS) in a frequency range 0.01 - 10E+5 Hz to 10 mV AC. The results show that the films of CS/PPy/MWCNT have a homogeneous distribution where the chitosan envelops the loads, while for EIS retention load was observed within the matrix observing these materials in accordance with the equivalent circuit of Warburg showing diffusional process.